Optimalisasi Pemasaran Produk Melalui Pemanfaatan Aplikasi Canva Sebagai Media Branding Dan Pendampingan Media Sosial Instagram Pada UMKM Catering “Miss Tote” Di Kelurahan Kepanjen Kidul, Kota Blitar - Devi Khoiriyah; Jojok Dwiridotjahjono (Jurnal Pengabdian Masyarakat Indonesia Sejahtera, 2023)
Catering "Miss Tote" is one of the MSMEs located in Kepanjen Kidul Village, Kepanjen Kidul District, Blitar City. In today's modern era, the catering business is faced with problems related to technology and digitalization. The implementation of community service aims to optimize product marketing through the use of the Canva application as a branding medium and mentoring the use of Instagram social media to expand customer reach and introduce products to potential customers. The method used is a case study with a qualitative approach, the data obtained from interviews with the owner of the MSMEs Catering "Miss Tote" and observations of marketing that has been done and documentation during the implementation process. The results of the study show that the "Miss Tote" MSMEs has marketing potential that has not been optimized, therefore students contribute to making logos, banners, catalogs and brochures as media branding of the "Miss Tote" MSMEs. Implementing a marketing strategy using Canva can have a positive impact such as building a strong brand image so that it can increase customer trust and become the hallmark of a business.